IMPROVEMENT OF THE FINANCIAL SECTOR PROFESSIONAL TRAINING AND DEVELOPMENT SYSTEM - Вознюк, Микола; Богів, Роман (Socio-economic relations in the digital society, 2019)
The article deals with the peculiarities of the evolution of the financial sector, the change in the methods of providing its services and the relationship with its customers. Taking into account the increasing requirements for personnel in the country’s financial system, new tasks for the system of training and development of personnel in the financial sector of the economy are outlined. Prospects and threats of technology usage in financial sector institutions are outlined. A SWOT analysis format was used to identify and identify strengths, weaknesses, opportunities and threats in the financial sector’s professional training. The basic competencies that should be inherent in the system of personnel support of the financial sector of the economy are formulated. A roadmap for the development of competences and vocational training for the financial sector of the economy is presented, which includes the stages of development, characterization of skills and competences, as well as the necessary measures for acquiring these competences. It is concluded that under the influence of rapid changes in the modern world, the formation of competencies of financial sector personnel requires the use of non-traditional methods. It is concluded that institutions of higher education must be positioned and actually function as sources of acquisition and accumulation of new, unique knowledge, and should meet the growing demands of «knowledge consumers».